2018
DOI: 10.1002/ece3.3807
|View full text |Cite
|
Sign up to set email alerts
|

Count data in biology—Data transformation or model reformation?

Abstract: Statistical analyses are an integral component of scientific research, and for decades, biologists have applied transformations to data to meet the normal error assumptions for F and t tests. Over the years, there has been a movement from data transformation toward model reformation—the use of non‐normal error structures within the framework of the generalized linear model (GLM). The principal advantage of model reformation is that parameters are estimated on the original, rather than the transformed scale. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…We did not perform yet the skewness tests of variables in the case of these regional datasets. Still, asymmetry was not a matter of concern for the corresponding models, since both the binary logistic regression [109] and the Poisson one with robust standard errors as a generalized linear model form of regression analysis [110] are proven to be robust when using non-normal data.…”
Section: Figurementioning
confidence: 99%
“…We did not perform yet the skewness tests of variables in the case of these regional datasets. Still, asymmetry was not a matter of concern for the corresponding models, since both the binary logistic regression [109] and the Poisson one with robust standard errors as a generalized linear model form of regression analysis [110] are proven to be robust when using non-normal data.…”
Section: Figurementioning
confidence: 99%
“…These models can be extended to relatively complex situations, including regression models, mixed-effects models, and models that accommodate overdispersion, underdispersion, and excess zeros. [1][2][3] However, in particular when very large counts are to be modeled, such as counts of viral or bacterial load in medical applications, [4][5][6][7] or large counts in biology and ecology, 8,9 researchers often log-transform the data. After doing so, the data might be expected to be normally distributed, at least approximately, and standard statistical procedures, such as normal linear models, including mixed-effects linear models, are applied.…”
Section: Introductionmentioning
confidence: 99%
“…ANOVA requires that the following assumptions be met: homogeneity of variances, normally distributed residuals and independent distributions. However, the data produced by experiments involving count data in the biological sciences often do not meet such assumptions (St-Pierre;Shikon;Schneider, 2018;Kosma et al, 2019), as seen in studies of seeds of genetically impoverished species, which present a high variability rate, such as forest seeds Araújo, 2018). Sileshi (2012) showed that in 429 studies with seed viability data published from 2002 to 2012, 70% of researchers used ANOVA to analyse the data, and among those who did, only 20% performed tests to verify the homogeneity of variances and normality of residuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, a particular transformation is not always available to satisfy all the assumptions of the analysis. In addition, data transformation creates difficulty in interpreting results due to a change in scale (St-Pierre;Shikon;Schneider, 2018). Thus, the reformulation of the statistical model at the expense of data transformation is an advantageous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation